Introduction to pronoun awareness (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. This track will cover Personal Gender Pronouns (PGPs). We'll look at what they are, give a brief overview of some important definitions, and then look at ways of sharing your pronouns and working to create a more inclusive work environment. Learning Objectives Learn what personal gender pronouns are Learn some important definitions around gender identity and pronouns Learn ways of sharing your pronouns and learning other people's Learn how to work to create a more inclusive work environment.